Linguistic Proficiency and Human Rights: The case for accent as a protected ground - Glougie, Jennifer (Language and Law / Linguagem e Direito, 2017)
The goal of this paper is to argue for the inclusion of linguistic proficiency as a protected ground in human rights law generally and, in particular, under the British Columbia Human Rights Code. Speciffically, I argue that L2 speakers are entitled to protection on the basis of their accent when they are required to operate in their L2. I outline the general law and policy with respect to human rights and argue that accent is analogous to those grounds explicitly protected in human rights legislation and should be protected as such. I outline the problems with the current approach from a linguistic perspective and show how the current approach is inconsistent with the goals of human rights law generally.